ENVIRONMENTAL STORYTELLING DALAM VISUALISASI TEMPAT KEJADIAN PERKARA (TKP) PADA BOARD GAME DETEKTIF: Environmental Storytelling in Crime Scene Visualization on a Detective Board Game - Ratu Sayyidah Nur Latifah; Rizki Taufik Rakhman; Siti Khodijah Lestari (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2026)
Environmental Storytelling in Crime Scene Visualization on a Detective Board Game. The Indonesian public currently has a low understanding of the importance of maintaining the status quo at a Crime Scene (TKP). Literature reviews indicate that educational media regarding Crime Scene Standard Operating Procedures (SOPs) in Indonesia remains highly limited and is dominated by rigid text-based formats such as scientific journals or blog articles. On the other hand, the low national literacy rate has become a significant concern for the government. This research aims to offer a novel approach through gamification media that integrates SOP mechanisms and crime scene preservation in homicide cases into a board game. The primary focus of this study is to explore the implementation of environmental storytelling in crime scene visualization to examine the extent to which visual elements can transcend decorative functions and actively serve as a medium for chronological narrative delivery. The research method employed is qualitative with a design thinking approach, supported by data collection through observation, interviews, literature studies, documentation, product trend analysis, Focus Group Discussions (FGD), and product testing. Research findings show that respondents successfully understood the investigative flow through detailed visual observation of the provided evidence objects. The results conclude that environmental storytelling is effective in transforming complex police technicalities into a comprehensible visual narrative within a detective board game. Nevertheless, the study identified a gap between visual legibility and the retention of the narrative SOP text among players. As a design implication, the development of a more systematic clue system and the integration of post-game evaluation mechanisms are highly recommended for future researchers.